Analisis Kebiasaan Aktivitas Belanja dan Keterlibatan Dalam Fashion terhadap Perilaku Pembelian Spontan di Yogyakarta - Hanan Wihasto (Journal of Economic and Management (JECMA), 2026)
The dynamics of the retail business economy in Indonesia show significant growth, which in turn has triggered the development of consumer lifestyles and shopping patterns characterized by increasingly high expectations—demanding more, expecting better quality, and seeking consistency. The problem encountered is that high-income consumers tend to exhibit fluctuating spending patterns, often exceeding the financial plans they have previously established. This study aims to examine the influence of Shopping Activity Habits and Fashion Involvement on Impulse Buying Behavior among consumers in Yogyakarta. The sample of this study consists of individuals residing in Yogyakarta who have their own income, monthly expenditures of at least IDR 3,000,000, and who have previously shopped at Ambarrukmo Mall, Pakuwon Mall, and Jogja City Mall. The analytical technique employed is multiple linear regression, which facilitates the examination of the role of Shopping Activity Habits and Fashion Involvement in influencing Impulse Buying Behavior. The results indicate that Hedonic Shopping Value and Fashion Involvement have a significant effect on impulse buying behavior among consumers in Yogyakarta.